Role of joint damage, malalignment and inflammation in articular tenderness in rheumatoid arthritis, psoriatic arthritis and osteoarthritis. Issue 7 (12th January 2021) - Gessl, Irina; Popescu, Mihaela; Schimpl, Victoria; Supp, Gabriela; Deimel, Thomas; Durechova, Martina; Hucke, Miriam; Loiskandl, Michaela; Studenic, Paul; Zauner, Michael; Smolen, Josef S; Aletaha, Daniel; et al.
Abstract : Objectives: To determine whether clinical tenderness can be considered a sign of inflammatory joint activity in patients with rheumatoid arthritis (RA), osteoarthritis (OA) or psoriatic arthritis (PsA) and to assess other possible factors associated with tenderness. Methods: Patients diagnosed with RA, PsA and OA underwent clinical and ultrasound examination of wrists and finger joints. Radiographs of the hands were scored for erosions, joint space narrowing (JSN), osteophytes and malalignment. A binary damage score (positive if ≥1 erosion, JSN and/or presence of malalignment) was calculated. Differences in grey scale signs of synovitis and power Doppler (PD) between tender non-swollen (TNS) versus non-tender non-swollen (NTNS) joints were calculated. Disease duration was assessed, <2 years was regarded as early and >5 years as long-standing arthritis. Results: In total, 34 patients (9 early and 14 long-standing) from patients with RA, 31 patients (7 early and 15 long-standing) with PsA and 30 with OA were included. We found equal frequencies of PD signal between TNS and NTNS joints in RA (p=0.18), PsA (p=0.59) or OA (p=0.96). However, PD had a significant association with tenderness in early arthritis both in RA (p=0.02) and in PsA (p=0.02). The radiographic damage score showed significant association with tenderness in RA (p<0.01), PsA (p<0.01) and OA (p=0.04). Conclusion: Tenderness might not always be a sign of active inflammation in RA, PsA and OA. While tenderness in early arthritis may be more related to inflammation, established disease is better explained by joint damage and malalignment.